1991
DOI: 10.1111/j.1365-2222.1991.tb01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells and allergic rhinitis

Abstract: Large scale surveys in general practice have indicated that the prevalence of hay fever is 4% and that the disease has becane more conmon in recent years. Patients attending their general practitioners for treatment prdbably represent less than half of those who suffer from the disease as many afflicted by seasonal rhinitis treat themselves. The disease is equally ccmmon in both sexes, its incidence being highest between the ages of 15 and 25 years [1]. While studies from Japan suggest that the increase in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the appearance of mediators, such as histamine, leukotrienes (B4, C4), and prostaglandins (D2), is followed by the typical hay fever symptoms of rhinorrhea, sneezing, itching, and nasal obstruction (6). These findings are consistent with mast cell degranulation (4). Specific provocation with histamine only also leads to the same symptoms, but within seconds (11).…”
mentioning
confidence: 63%
“…Previous studies have shown that the appearance of mediators, such as histamine, leukotrienes (B4, C4), and prostaglandins (D2), is followed by the typical hay fever symptoms of rhinorrhea, sneezing, itching, and nasal obstruction (6). These findings are consistent with mast cell degranulation (4). Specific provocation with histamine only also leads to the same symptoms, but within seconds (11).…”
mentioning
confidence: 63%